Overexpression of neuropeptide Y decreases responsiveness to neuropeptide Y. (February 2020) - Corder, Katelynn M.; Li, Qin; Cortes, Mariana A.; Bartley, Aundrea F.; Davis, Taylor R.; Dobrunz, Lynn E.
Abstract: Neuropeptide Y (NPY) is an endogenous neuropeptide that is abundantly expressed in the central nervous system. NPY is involved in various neurological processes and neuropsychiatric disorders, including fear learning and anxiety disorders. Reduced levels of NPY are reported in Post-Traumatic Stress Disorder (PTSD) patients, and NPY has been proposed as a potential therapeutic target for PTSD. It is therefore important to understand the effects of chronic enhancement of NPY on anxiety and fear learning. Previous studies have shown that acute elevation of NPY reduces anxiety, fear learning and locomotor activity. Models of chronic NPY overexpression have produced mixed results, possibly caused by ectopic NPY expression. NPY is expressed primarily by a subset of GABAergic interneurons, providing specific spatiotemporal release patterns. Administration of exogenous NPY throughout the brain, or overexpression in cells that do not normally release NPY, can have detrimental side effects, including memory impairment. In order to determine the effects of boosting NPY only in the cells that normally release it, we utilized a transgenic mouse line that overexpresses NPY only in NPY+ cells. We tested for effects on anxiety related behaviors in adolescent mice, an age with high incidence of anxiety disorders in humans. Surprisingly, we did not observe the expected reduction in anxiety-like behavior in NPY overexpression mice. There was no change in fear learning behavior, although there was a deficit in nest building. The effect of exogenous NPY on synaptic transmission in acute hippocampal slices was also diminished, indicating that the function of NPY receptors is impaired. Reduced NPY receptor function could contribute to the unexpected behavioral outcomes. We conclude that overexpression of NPY, even in cells that normally express it, can lead to reduced responsiveness of NPY receptors, potentially affecting the ability of NPY to function as a long-term therapeutic. Highlights: Cell-type specific NPY overexpression impairs nest building in adolescent mice. NPY overexpression does not reduce anxiety-like behavior. NPY overexpression does not change fear learning or extinction. Effects of NPY overexpression are the same in adolescent male and female mice. NPY overexpression impairs NPY receptor function at temporoammonic-CA1 synapses.